2018
DOI: 10.1016/j.biortech.2018.08.111
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of backwashing effectiveness in membrane bioreactor (MBR) based on different membrane fouling stages

Abstract: In this study the effect of different fouling stages of hollow fiber membranes on effective backwashing length in MBR has been investigated. Computational fluid dynamics (CFD) is imported to simulate backwashing process. A multi-physics coupling model for free porous media flow, convective mass transfer and diluted species transport was established. The laser bijection sensors (LBS) were imported to monitor the backwashing solution position inside fiber lumen. Simulation results indicated that membrane fouling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The sludge suspension concentration was obtained by the weighing method. 33 16S rRNA sequencing and metagenomics were used to analyze the microbial population structure based on Illumina high-throughput sequencing platforms according to prescribed methods. 16S rRNA sequencing mainly included the following steps.…”
Section: Methodsmentioning
confidence: 99%
“…The sludge suspension concentration was obtained by the weighing method. 33 16S rRNA sequencing and metagenomics were used to analyze the microbial population structure based on Illumina high-throughput sequencing platforms according to prescribed methods. 16S rRNA sequencing mainly included the following steps.…”
Section: Methodsmentioning
confidence: 99%
“…Cui, Wang, et al (2018) used CFD to simulate backwash in MBRs. Results indicated that the degree of membrane fouling changed the velocity of the backwash solution, affecting the optimum backwash length.…”
Section: Membrane Foulingmentioning
confidence: 99%
“…An effective backwash strategy can delay irreversible fouling and reduce the overall cost associated with UF foulants [10][11][12]. Backwash duration and frequency are important parameters [13][14][15] that influence fouling and cannot be determined solely based on the supplier's recommendations [16]. Most MBR plants operate at a constant flux, and fouling is generally indicated by an increase in transmembrane pressure (TMP) over time.…”
Section: Introductionmentioning
confidence: 99%